Adsorbsi Ion Logam Cu (II) Menggunakan Biomassa Daun Genjer (Limnocharis flava): Adsorption of Cu (II) Ions by Biomass of Genjer Leaves (Limnocharis flava) - Helni Febriani; Dwi Juli Puspitasari; Ruslan; Husain Sosidi (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
The adsorption of Cu (II) ions by Genjer (Limnocharis flava) biomass has been carried out. This research aims to determine the optimum pH of the plant and the contact time between the metal ion Cu (II) with the plant that produces the highest absorption, as well as knowing the best adsorbent mass for absorption between Cu (II) metal ions and genjer plants. The study used a completely randomized design (CRD) with variables of pH, contact time, and adsorbent mass. The testing of the absorption of the Genjer leaves biomass against Cu (II) was carried out with Atomic Adsorption Spectrophotometric (AAS). The results showed that the optimum absorption produced was 83.34% at pH 4, and 91.54% with the highest contact time of 30 minutes, and 82.04% with an adsorbent mass of 1 gram. Keywords: Limnocharis flava, pH, contact time, adsorbent mass, adsorption, Cu (II) ion